Pengaruh Harga, Reputasi Vendor Dan Ulasan Produk Terhadap Keputusan Pembelian Di Tokopedia (Studi Kasus Mahasiswa FEB Universitas Islam Malang) - Muhammad Abdulah Zamzamy; Nur Hidayati; Afi Rahmat Slamet (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis study was conducted to determine how much influence the variables Price, Supplier reputation and Product ratings have on purchasing decisions. Case study on FEB UNISMA students. A sample of 88 people was taken in this study. The sampling method is from people who bought products on Tokopedia. To find out the data that will be investigated later, this study uses a questionnaire to better understand each person's opinion by completing the statements attached to the questionnaire.In addition, this research uses the SPSS measurement instrument to test data in the form of instrument tests, multiple linear regression analysis, classical assumption tests and hypothesis tests. From this research, it can be concluded that the variable price, supplier reputation and product reviews simultaneously or jointly influence purchasing decisions on Tokopedia. Meanwhile, in part or separately from each independent variable, that the price and reputation of the supplier do not influence purchasing decisions, while product ratings influence purchasing decisions.Keywords: price, supplier reputation, purchasing decision